ETIKA DAN KEJUJURAN DALAM BERPOLITIK - Prihatin Dwi Hantoro, Prihatin Dwi Hantoro (Program Magister Ilmu Politik, Universitas Diponegoro, 2013)
Abstract Talking about the ethics of participating in politics in the life of a nation and a country, we have to admit that nowadays many among the political elite tends to be politicking with ethical dereliction of outstanding statesmanship. An awful lot of the fact that their politicking done without rationality, emotions and putting forward the interests of the group, and does not give priority to the interests of a nation. Politics is not a purely pragmatic nature of case, which concerns only a goal and how to achieve those goals, that can be handled with rationality. Looks more like a political ethics demand that a destination that is selected must be justified by common sense that can be tested, and how to achieve them must be defined can be tested with the moral criteria. Honesty in politics is very important in the efforts to improve the situation of the nation is full of falsehoods. High low moral integrity of a person in politics to determine high low integrity of the personality and the quality of the politicking politicians. With still having our politicians are unscrupulous, allowing us to hope for improvement of politics and morality that are dilapidated. Keywords: ethics, politics, honesty